Basic student nurse perceptions about clinical instructor caring - Gerda-Marie Meyer; Elsabe Nel; Charlene Downing (AOSIS, 2016)
Background: Caring is the core of nursing and should be cultivated in student nurses. However, there are serious concerns about the caring concern in the clinical environment and in nursing education. Clinical instructors are ideally positioned to care for student nurses so that they in turn, can learn to care for their patients. Methods: A descriptive, comparative, cross-sectional and correlational quantitative research design with convenience sampling was conducted to describe the perceptions of junior student nurses (n = 148) and senior student nurses (n = 168) regarding clinical instructor caring. A structured self administered questionnaire using the Nursing Student Perceptions of Instructor Caring (NSPIC) (Wade & Kasper, 2006) was used. Descriptive statistics and hypotheses testing using parametric and non parametric methods were conducted. The reliability of the NSPIC was determined. Results: Respondents had a positive perception of their clinical instructors' caring. No relationship could be found between the course the respondents were registered for, the frequency of contact with a clinical instructor, the ages of the respondents and their perceptions of clinical instructor caring. The NSPIC was found to be reliable if one item each from two of the subscales were omitted. Conclusions: Student nurses perceived most strongly that a caring clinical instructor made them feel confident, specifically when he/she showed genuine interest in the patients and their care, and when he/she made them feel that they could be successful.